Mechanical Behavior of Oxide Dispersion Strengthened Steel Directly Consolidated by Rotary Swaging - Kocich, Radim; Kunčická, Lenka; Král, Petr; Dvořák, Karel (Materials (Basel, Switzerland), 2024)
Among the main benefits of powder-based materials is the possibility of combining different constituents to achieve enhanced properties of the fabricated bulk material. The presented study characterizes the micro- and sub-structures and related mechanical properties of ferritic steel strengthened with a fine dispersion of nano-sized Y2O3 oxide particles. Unlike the typical method of preparation via rolling, the material presented herein was fabricated by direct consolidation from a mixture of powders using the versatile method of hot rotary swaging. The mechanical properties were evaluated at room temperature and also at 1300 °C to document the suitability of the prepared steel for high-temperature applications. The results showed that the imposed shear strain, i.e., swaging ratio, is a crucial parameter influencing the microstructure and, thus, material behavior. The workpiece subjected to the swaging ratio of 1.4 already exhibited a sufficiently consolidated structure with ultra-fine grains and featured high room-temperature microhardness values (up to 690 HV0.5), as well as a relatively high maximum flow stress (~88 MPa) when deformed at the temperature of 1300 °C with the strain rate of 0.5 s-1. However, the dispersion of oxides within this sample exhibited local inhomogeneities. Increasing the swaging ratio to 2.5 substantially contributed to the homogenization of the distribution of the Y2O3 oxide particles, which resulted in increased homogeneity of mechanical properties (lower deviations from the average values), but their lower absolute values due to the occurrence of nucleating nano-sized recrystallized grains.
Keywords: direct consolidation; microhardness; microstructure; oxide dispersion strengthening; rotary swaging